IMPLEMENTASI QUALITY CONTROL CIRCLE (QCC) UNTUK MENINGKATKAN PRODUKTIVITAS RECOILING LINE - Alfiya Rokhmah (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
After going through the covid 19 pandemic, all companies began to rise to continue their business. one of them is a steel company which is a supplier of car-making materials to automotive companies. In 2021 the production of the Recoiling Line (RCL) was unable to reach the production target. Then it was traced again using field data and found that there had been a lot of downtime. After being identified, it was found that there were increasing cases of looping on the Pay Off Reel (POR) machine. This problem resulted in downtime of 32% thereby slowing down the production process at RCL. The purpose of this research is to find out the causes of looping in POR when under winding. The Quality Control Circle (QCC) method is often used in companies to implement continuous improvement. The results of this study are that the factors causing looping in the POR can be found during underwinding and can provide suggestions for improvements to reduce the frictional force between the coil and the Equipment guide table and the pressure between the coil car on the coil which results in looping on the POR machine so as to eliminate downtime due to looping of 121 minutes/month to 0 and can increase RCL production capacity by 0.3%/month with a saving cost of 162 million/year.